2023
DOI: 10.1186/s40170-023-00302-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals metabolic features of consolidation therapy in pediatric acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) and its treatment continue to pose substantial risks. To understand ALL more deeply, the metabolome in fasting plasma of 27 ALL patients before and after high-dose methotrexate therapies (consolidation therapy) including methotrexate and 6-mercaptopurine (6-MP) was investigated. Plasma metabolites were analyzed using liquid chromatography–tandem mass spectrometry (LC–MS). Orthogonal projections to latent structures discriminant analysis and significance analysis of microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Drug resistance is associated with various factors, and mitochondrial dysfunction is one of them. Targeting mitochondria has been a strategy for anti‐cancer therapy 31 and many studies confirmed its potential use as a treatment option for leukemia patients 9,10,32 . Therefore, targeting ALR may alter the mitochondrial function in T‐ALL which may prevent drug resistance in T‐ALL cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug resistance is associated with various factors, and mitochondrial dysfunction is one of them. Targeting mitochondria has been a strategy for anti‐cancer therapy 31 and many studies confirmed its potential use as a treatment option for leukemia patients 9,10,32 . Therefore, targeting ALR may alter the mitochondrial function in T‐ALL which may prevent drug resistance in T‐ALL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance is a crucial element of the relapse 7,8 and how to sensitize cancer cells to drugs' treatments is a question to ponder. Mitochondria are one such important target in ALL treatment, 9 and targeting mitochondrial respiration improves T‐ALL cells' sensitivity to chemotherapy 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare the quality control (QC) samples, we pooled ten microliters of each sample. The extraction procedure for the QC samples was performed in the same manner as described earlier [32].…”
Section: Methodsmentioning
confidence: 99%